2019
DOI: 10.1097/cm9.0000000000000143
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of weight adjusted bone mineral content in osteoporosis diagnosis in Chinese female population

Abstract: Background: Areal bone mineral density (aBMD) applied for osteoporosis diagnosis unavoidably results in the missingdiagnosis in patients with large bones and misdiagnosis in those with small bones. Therefore, we try to find a new adjusted index of bone mineral content (BMC) to make up shortcomings of aBMD in osteoporosis diagnosis. Methods: In this multi-center epidemiological study, BMC and aBMD of lumbar spines ( n = 5510) and proximal femur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…Third, previous studies reported that density conversion and inhomogeneity correction were probably more accurately determined using dual-energy CT subtraction, a procedure still being investigated and not in routine use at our institution. [ 36 39 ] Fourth, our results must be validated before they can be applied to plans other than VMAT. Since it has been reported that the effects of CAs decrease as the number of incident beams increases, in IMRT plans with less control points, the underestimation might be even graver.…”
Section: Discussionmentioning
confidence: 99%
“…Third, previous studies reported that density conversion and inhomogeneity correction were probably more accurately determined using dual-energy CT subtraction, a procedure still being investigated and not in routine use at our institution. [ 36 39 ] Fourth, our results must be validated before they can be applied to plans other than VMAT. Since it has been reported that the effects of CAs decrease as the number of incident beams increases, in IMRT plans with less control points, the underestimation might be even graver.…”
Section: Discussionmentioning
confidence: 99%
“…The BMD results were expressed in g/ cm. 2 The femur was scanned by Skyscan (Brooke micro CT, Kentucky, Belgium) and analyzed by Skyscan software. The measurement was performed with 40 kV and 250 μA.…”
Section: Bmd Measurement and Bone Histomorphometric Analysismentioning
confidence: 99%
“…1 Among women over 60 in China, the prevalence of osteoporosis is as high as 40% −50%, of which about 30% −50% experience osteoporosis-related fractures. 2 It seriously affects the physical health and life quality, and even lead to shortened life span. 3 And osteoporosis and its related fractures seriously increase the financial and human burden of the country and family.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor: We appreciate the attentive and interesting article “ Efficacy of weight adjusted bone mineral content in osteoporosis diagnosis in Chinese female population ” written by Liu et al [1] The authors have nicely shown bones are three dimensional tissues, only volumetric bone mineral density (vBMD) can be regarded as completely standardized, since the areal bone mineral density (aBMD) is two-dimensional and could result in missed diagnosis in subjects with large bones and misdiagnosis in those with small bones. In addition, although vBMD has undeniable advantages, the most sophisticated dual-energy X-ray absorptiometry (DXA) instrument is not able to measure the bone volume in vivo .…”
mentioning
confidence: 99%
“…Based on the regression coefficient, the researchers proposed “analysis self-assessment tool for Asia (OSTA),” with the formula of OSTA score = (weight – age) × 0.2, and populations with an OSTA score less than or equal to 4 was considered high-risk for the osteoporosis, which has been applied in many Asian countries. However, Gu et al [1] wrote in the article that OSTA score less than or equal to 5 is considered as a high risk of osteoporosis, so the value of 5 in this sentence should be changed to 4 to be more appropriate. In addition, Koh et al [3] and some studies have also shown that age has a great correlation with bone mineral content (BMC), so should age be considered in wBMC?…”
mentioning
confidence: 99%